The Czech Surveillance System for Invasive Pneumococcal Disease, 2008-2013: A Follow-Up Assessment and Sensitivity Estimation - Stock, Nina Katharina; Maly, Marek; Sebestova, Helena; Orlíková, Hana; Kozakova, Jana; Krizova, Pavla (PLoS One, 2015)
BACKGROUND: Invasive pneumococcal disease (IPD) is caused by Streptococcus pneumoniae and mostly presents as pneumonia, sepsis or meningitis. A notable portion of IPD cases is vaccine preventable and the pneumococcal conjugate vaccine (PCV) was introduced into the routine childhood immunization programs in many countries during the last decades. OBJECTIVES: Before PCV introduction in the Czech Republic in 2010, a national surveillance system for IPD was implemented in 2008 and further improved in 2011. In this study, we describe the new surveillance system for the first time and measure its sensitivity between 2010 and 2013 using the capture-recapture method. Furthermore, we describe the recent epidemiological trend of IPD, taking sensitivity estimates into account. RESULTS AND CONCLUSIONS: Between 2010 and 2013 the estimated sensitivity of the overall IPD surveillance increased from 81% to 99%. The sensitivity of individual reporting sources increased from 72% to 87% for the laboratory system and from 31% to 89% for the epidemiological notification system. Crucial for this improvement was the introduction of quarterly report reminders in 2011. Due to positive source dependency, the presented sensitivity estimates are most probably overestimated and reflect the upper limit of reporting completeness. Stratification showed variation in sensitivity of reporting particularly according to region. An effect of the PVC vaccination in the Czech Republic is visible in the incidence of IPD in target age groups (<5 y). This influence was not evident in the total IPD incidence and may interfere with increasing sensitivity of reporting. In 2013, an increase in the IPD incidence was observed. This finding requires further observation and a detailed vaccine impact analysis is needed to assess the current immunization strategy.
Keywords: Pneumococcal Vaccines; programy národního zdraví; Vaccines, Conjugate; vakcíny konjugované; Biostatistics; Humans; následné studie; očkovací schéma; Czech Republic; National Health Programs; pneumokokové infekce; pneumokokové vakcíny; Follow-Up Studies; incidence; Immunization Schedule; Česká republika; epidemiologické monitorování; Immunization Programs; Pneumococcal Infections; Mass Vaccination; Epidemiological Monitoring; očkovací programy; hromadná vakcinace; lidé; biostatistika; Incidence